Analysis of telehealth acceptance for basic life support training in sudden cardiac arrest in Pontianak - Ruhil Iswara; Sri Kusumadewi; Rahadian Kurniawan (Institute of Advanced Engineering and Science, 2025)
Sudden cardiac arrest (SDA), which is one of the most prevalent causes of mortality, can be prevented by quickly conducting basic life support (BLS). In Pontianak City, the challenges associated with obtaining emergency health training, such as BLS, remain high. This study aims to evaluate user acceptance of telehealth as well as its effectiveness in BLS training. We will also discuss its impact on community knowledge and skills in managing cardiac arrest. We used the HOT-Fit method to analyze the level of acceptance of telehealth in BLS training. We collected data from 60 respondents who underwent telehealth-based BLS training. The results showed that participants' understanding and readiness in dealing with heart attack emergencies had increased significantly, by 90% and 92%, respectively. Analysis of the level of acceptance with HOT-Fit showed that system quality had the greatest influence on system use (0.611). Service quality exerted the most significant impact on user satisfaction (0.568). The net benefit was influenced by system use, user satisfaction, and organizational support, with user satisfaction having the greatest influence (0.600). Further research will be conducted on the utilization of augmented reality (AR) or virtual reality (VR) technology to implement telehealth for BLS training.